Fluorescence energy transfer as a probe for nucleic acid structures and sequences. - Mergny, J L (1994)
The primary or secondary structure of single-stranded nucleic acids has been investigated with fluorescent oligonucleotides, i.e., oligonucleotides covalently linked to a fluorescent dye. Five different chromophores were used: 2-methoxy-6-chloro-9-amino-acridine, coumarin 500, fluorescein, rhodamine and ethidium. The chemical synthesis of derivatized oligonucleotides is described. Hybridization of two fluorescent oligonucleotides to adjacent nucleic acid sequences led to fluorescence excitation energy transfer between the donor and the acceptor dyes. This phenomenon was used to probe primary and secondary structures of DNA fragments and the orientation of oligodeoxynucleotides synthesized with the alpha-anomers of nucleoside units. Fluorescence energy transfer can be used to reveal the formation of hairpin structures and the translocation of genes between two chromosomes.